The Concept of Digital Waqf As a Mindful Spending Lifestyle For Generation Z in The Digital Era - Misi Anggraini (Universitas Negeri Surabaya, 2025)
As a lifestyle of mindful spending among Generation Z in the digital era. The research employs qualitative methods, including literature review and interviews, to understand how digital waqf influences financial behavior and religious practices. The findings indicate that digital waqf fosters a sense of social responsibility and spiritual mindfulness, encouraging prudent financial management and active participation in charitable acts through digital platforms. The discussion highlights the integration of Islamic economic principles with contemporary digital trends, emphasizing the potential of digital waqf to promote ethical consumption and social awareness. This research contributes to the understanding of innovative Islamic financial practices aligned with Millennials’ and Generation Z’s digital engagement, suggesting a shift towards more conscious and ethical spending habits in the digital age.